Seasonality in Primates : Studies of Living and Extinct Human and Non-Human Primates - Brockman, Diane K.; Van Schaik, Carel P. (Cambridge : Cambridge University Press, 2005)
The emergence of the genus Homo is widely linked to the colonization of "new" highly seasonal savannah habitats. However, until now, our understanding of the possible impact of seasonality on this shift has been limited because we have little general knowledge of how seasonality affects the lives of primates. This book documents the extent of seasonality in food abundance in tropical woody vegetation, and then presents systematic analyses of the impact of seasonality in food supply on the behavioural ecology of non-human primates. Syntheses in this volume then produce for the first time broad generalizations concerning the impact of seasonality on behavioural ecology and reproduction in both human and non-human primates, and apply these insights to primate and human evolution. Written for graduate students and researchers in biological anthropology and behavioural ecology, this is an absorbing account of how seasonality may have affected an important episode in our own evolution.
Cover; Half-title; Series-title; Title; Copyright; Contents; Contributors; Preface; Part I Introduction; Part II Seasonal habitats; Part III Seasonality and behavioral ecology; Part IV Seasonality, reproduction, and social organization; Part V Seasonality and community ecology; Part VI Seasonality and human evolution; Index.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Primates -- Seasonal variations -- Congresses; Primates -- Evolution -- Congresses; Human evolution -- Congresses; Primates -- Physiology; Seasons; Animal behavior -- Physiology; Ecology; Evolution; Physiology, Comparative; Evolution (Biology); Primates -- physiology; Seasons; Behavior, Animal -- physiology; Biological Evolution; Ecology; Physiology, Comparative; Primates -- Variations saisonnières -- Congrès.; Primates -- Évolution -- Congrès.; Êtres humains -- Évolution -- Congrès.; Primates -- Physiologie; Saisons; Évolution.; Physiologie comparée.; Évolution (Biologie); Écologie.; evolution; ecology; NATURE -- Animals -- Mammals; SCIENCE -- Life Sciences -- Zoology -- Mammals; Evolution (Biology); Ecology; Evolution; Human evolution; Physiology, Comparative; Primates -- Evolution; Primates -- Physiology; Seasons; Primate seasonality; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.